2010
DOI: 10.1038/jp.2010.103
|View full text |Cite
|
Sign up to set email alerts
|

Resistin levels in preterms: are they influenced by fetal inflammatory course?

Abstract: Objective: Many different factors are involved in the pathogenesis of preterm deliveries and among them maternal or perinatal infections and inflammatory response have the major role. Researches were carried out about resistin, which is thought to have a role in inflammatory cytokine cycle and it was shown to be associated with growth in neonates. However, no research has been carried out showing its relationship with inflammation in neonates. In this study, we aimed to evaluate the resistin levels in prematur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Resistin levels are higher in cord blood from preterm compared to full-term pregnancies (Martos-Moreno et al, 2009), which could be due to the higher prevalence of a proinflammatory environment in preterm pregnancies, as observed in cases with prelabor rupture of the placental membranes (Gursoy, Aliefendioglu, Caglayan, Aktas, & Ovali, 2011). This is supported by the positive correlation between resistin and proinflammatory cytokine levels in cord blood, as well as by the suppression of resistin observed in mothers receiving antenatal steroids (Gursoy et al, 2011;Martos-Moreno et al, 2009).…”
Section: Resistinmentioning
confidence: 91%
“…Resistin levels are higher in cord blood from preterm compared to full-term pregnancies (Martos-Moreno et al, 2009), which could be due to the higher prevalence of a proinflammatory environment in preterm pregnancies, as observed in cases with prelabor rupture of the placental membranes (Gursoy, Aliefendioglu, Caglayan, Aktas, & Ovali, 2011). This is supported by the positive correlation between resistin and proinflammatory cytokine levels in cord blood, as well as by the suppression of resistin observed in mothers receiving antenatal steroids (Gursoy et al, 2011;Martos-Moreno et al, 2009).…”
Section: Resistinmentioning
confidence: 91%
“…Correlations between resistin levels and other inflammatory markers, including IL-6, leptin, TNF-α, CRP, and PCT, have been reported in patients with severe inflammatory disease, sepsis, and septic shock. [9][10][11][12][13][14][15] To our knowledge, no study to date has evaluated the diagnostic value of resistin in sepsis in preterm infants. Therefore, we aimed to evaluate the potential of resistin in the diagnosis of sepsis in preterm infants, for comparison with CRP results, and to evaluate the resistin levels in gramnegative sepsis (GNS) and gram-positive sepsis (GPS).…”
mentioning
confidence: 99%
“…In a study by Martos-Moreno et al [48], preterm neonates had higher resistin levels than full-term neonates. Conversely, some authors observed decreased resistin concentrations in preterm infants, compared with full-term infants [60], whereas resistin levels were not correlated with GA in another study [61]. Beyond birth, some reports found that resistin levels were similar between preterm and full-term children at school age [53,62].…”
Section: Discussionmentioning
confidence: 87%